Post-traumatic bronchobiliary fistula. Issue 4 (5th April 2019) - Banerjee, Niladri; Rattan, Amulya; Priyadarshini, Pratyusha; Kumar, Subodh
Abstract : Post-traumatic bronchobiliary fistula (BBF) is a rare entity, with only a few cases reported worldwide. Bilioptysis is pathognomonic of the condition, however, bronchoscopy and bronchoalveolar lavage along with CT are used for confirmation. We describe this condition in a young woman who presented to us with bilioptysis following a laparotomy for blunt torso trauma. Diagnosis was made of BBF, followed by surgical management and complete recovery. We emphasise the signs of early diagnosis, confirmatory tests, individualised treatment and advocate surgical management as the gold standard of treatment.